2016
DOI: 10.1007/s10797-015-9390-z
|View full text |Cite
|
Sign up to set email alerts
|

State ownership and corruption

Abstract: Using data from the World Bank's Enterprise Surveys, we test two interesting results that emerge from the theoretical model presented in Shleifer and Vishny (1994) that studies bargaining between politicians and managers of state-owned firms. Shleifer and Vishny's model suggests that firms with more state ownership should tend to pay less in bribes but not have a different experience of costly obstacles imposed on them by politicians. In our full sample, the results suggest that a one percent increase in state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Third, we control for firm size using the natural logarithm of sales (see Fan et al, 2009). Fourth, we include a variable which measures the extent of state ownership (see Fan et al, 2009;Billon and Gillanders, 2014). 4 Like our foreign ownership variable, state-owned companies have access to different social and political networks, potentially affecting the level of bribery.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we control for firm size using the natural logarithm of sales (see Fan et al, 2009). Fourth, we include a variable which measures the extent of state ownership (see Fan et al, 2009;Billon and Gillanders, 2014). 4 Like our foreign ownership variable, state-owned companies have access to different social and political networks, potentially affecting the level of bribery.…”
Section: Methodsmentioning
confidence: 99%
“…In general, greater decentralization of the government (with physical and fiscal decentralization considered by alternate studies) is shown to lower corruption through its promotion of greater transparency. A larger government size might imply state ownership of certain enterprises and that has been shown to link with corrupt activity (Billion and Gillanders, 2016). The results with respect to the impact of government size are more mixed in the literature, with evidence consistent with an increase in corruption via an increase in bureaucratic red tape (Goel and Nelson, 1998) and with a decrease in corruption, via a larger government size, partly associated with more checks and balances (Goel and Nelson, 2010).…”
Section: Literaturementioning
confidence: 99%
“…The World Bank takes several precautions in its surveys to reduce measurement errors in the Bribe variable. First, in line with the empirical research on the corruption theme, the question refers to 'establishments like this' to help provoke truthful responses (Billon & Gillanders, 2016). This indirect formulation of the question implies that respondents are not asked to confess that their establishment has paid bribes but to gauge the behavior of similar types of establishment.…”
Section: Data and Samplementioning
confidence: 99%